The role and mechanism of Aβ clearance dysfunction in the glymphatic system in Alzheimer’s disease comorbidity - Li, Hailang; Yao, Qianqian; Huang, Xueyan; Yang, Xiaoyan; Yu, Changyin (Frontiers in Neurology, 2024)
Alzheimer’s disease (AD) is the leading type of dementia globally, characterized by a complex pathogenesis that involves various comorbidities. An imbalance in the production and clearance of amyloid β-protein (Aβ) peptides in the brain is a key pathological mechanism of AD, with the glymphatic system playing a crucial role in Aβ clearance. Comorbidities associated with AD, such as diabetes, depression, and hypertension, not only affect Aβ production but also impair the brain’s lymphatic system. Abnormalities in the structure and function of this system further weaken Aβ clearance capabilities, and the presence of comorbidities may exacerbate this process. This paper aims to review the role and specific mechanisms of impaired Aβ clearance via the glymphatic system in the context of AD comorbidities, providing new insights for the prevention and treatment of AD. Overall, the damage to the glymphatic system primarily focuses on aquaporin-4 (AQP4) and perivascular spaces (PVS), suggesting that maintaining the health of the glymphatic system may help slow the progression of AD and its comorbidities. Additionally, given the ongoing controversies regarding the structure of the glymphatic system, this paper revisits this structure and discusses the principles and characteristics of current detection methods for the glymphatic system.